Analisis Pengaruh Risiko Bisnis, Risiko Keuangan, dan Risiko Pasar Terhadap Struktur Modal - Siska Yuli Anita; Hugo Prasetyo Winotoatmojo; Bambang Sugeng Dwiyanto; Alfiana; Abdul Rosid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of business risk, financial risk, and market risk on the capital structure of companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The data used in this study are secondary data in the form of annual financial reports. The sampling technique used in this study is the purposive sampling method with the number of companies used as samples being 30 companies, but 14 companies that meet the criteria. The analysis method used in this study is multiple linear regression analysis using the Statistical Product and Service Solution (SPSS) program application. The results of this study indicate that business risk has no effect on capital structure. While financial risk and market risk affect capital structure.